METABOLISM AND MECHANISM OF TOXICITY OF SELENIUM-CONTAINING SUPPLEMENTS USED FOR OPTIMIZING HUMAN SELENIUM STATUS - P. A. Poluboyarinov; D. G. Elistratov; V. I. Shvets (Тонкие химические технологии, 2019)
The work presents a review devoted to the metabolism and the mechanism of toxicity of seleniumcontaining supplements: elemental selenium, sodium selenite, diacetophenonyl selenide, selenopyrane, ebselen, dimethyl dipyrasolyl selenide and selenium-containing amino acids used for correction of selenium deficiency. Elemental selenium penetrating through cell walls, but not through transport channels demonstrates poorly predicted and difficultly regulated bioavailability. Sodium selenate is known to be the most toxic form of selenium in food. The metabolism of xenobiotic diacetophenonyl selenide resembles that of sodium selenide. The xenobiotic reacts with thiols, for instance, with the reduced form of glutathione leading to the formation of hydrogen selenide. Ebselen is not considered to be a well bioavailable form of selenium and thus possesses low toxicity. Xenobiotic selenopyrane eliminates selenium only in processes of xenobiotic liver exchange, and in our investigations - partially in acid-catalyzed hydrolysis. The metabolism of xenobiotic dimethyl dipyrasolyl selenide having low toxicity is poorly investigated. The toxicity of high doses of selenomethionine is determined by the possibility of incorporation in proteins and vitally important enzymes with dramatic changes of protein quaternary structure. The toxicity of high doses of methylselenocysteine seems to be caused by the lack of an exchange pool in the body and quick regeneration of hydrogen selenide from methylselenol which is formed as a result of enzymatic destruction of this amino acid. Also the issue of the most prospect selenium donor is discussed. The physiological compatibility, the low toxicity, the presence of an exchangeable pool in the organism, the antioxidantal properties and the simplicity of production indicate selenocystine as an optimal selenium donor.